Comprehensive comparative analysis of chloroplast genomes from seven Panax species and development of an authentication system based on species-unique single nucleotide polymorphism markers - Nguyễn, Văn Bình (2022)
Panax species are important herbal medicinal plants in the Araliaceae family. Recently, we reported the complete chloroplast genomes and 45S nuclear ribosomal DNA sequences from seven Panax species, two (P . quinqu e folius and P . trifolius) from North America and five (P . ginseng, P . notoginseng, P . japonicus, P . vietnamensis, and P . stipuleanatus) from Asia.